The impact of digitalization on food security in G20 countries: An empirical assessment - Singh, Ajay Kumar; Mishra, Vikash Kumar; C, Dhanya (Asian Journal of Agriculture and Rural Development, 2025)
This study assesses the impact of digitalization on food security (FS) and its dimensions in G20 countries. Descriptive statistical techniques are applied to create a food security index (FSI) and a digital development index (DDI). The FSI is considered as a combination of its dimensions, and the DDI is the integration of 16 indicators that foster appropriate digital development (DD). Log-linear regression models are introduced to examine the coefficient of DDI with FSI and specific variables. The study employs country-wise balanced panel data from 2010 to 2022. It reports significant variation in DD and FS across G20 countries. DD has a positive and statistically significant impact on FS and its other drivers. Furthermore, FS and its four dimensions have positive and bi-directional relationships with DD. FS and its other drivers, except for food utilization, are positively associated with forest area. Protection of ecosystem services is necessary to increase FS. Environmental technologies are also found to positively influence FS. Gross domestic savings appear useful for increasing FS. Environmental technologies, foreign direct investment, and gross savings show a positive impact on DD. Moreover, all dimensions of FS are favorable for promoting DD. The findings provide multiple policy implications for improving FS and DD in G20 countries.